Isoscopoletin inhibits hepatocellular carcinoma cell proliferation via regulating glycolysis-related proteins. - Chenyao Ruan; Chen Wang; Jiawen Gu; Zhihui Zhu (PLoS ONE)
Objective Isoscopoletin is one of the primary metabolites of natural product scoparone, which was reported to against tumor proliferation. The aim of this study was to explore the mechanism of isoscopoletin against hepatocellular carcinoma (HCC). Methods Transcriptomics was used to reveal the possible pathways of isoscopoletin against HCC in vitro. The potential targets of isoscopoletin against HCC through affecting glycolysis were analyzed by network pharmacology, then the potential binding abilities of isoscopoletin to glycolysis-related proteins were initially verified by high throughput virtual molecular docking. The affinities of isoscopoletin for glycolysis-related proteins were assayed using microscale thermophoresis (MST), which was reverse-validated by inhibiting the binding ability of isoscopoletin to GPD2. Glucose consumption and lactate production were examined to evaluate the effects of isoscopoletin on intracellular glycolysis, and the regulation of glycolysis-related targets by isoscopoletin was detected using RT-qPCR and ELISA kits. Results The results of transcriptomics showed that the differentially expressed genes (DEGs) were mainly enriched in glycolysis and other metabolic-related pathways. Network pharmacology and molecular docking revealed that GPD2, GPI, HSP90AA1 and PGK2 were the core targets in the glycolysis process of isoscopoletin against HCC. MST results showed that there was a strong affinity between isoscopoletin and GPD2, GPI, Hsp90α and PGK2. In vitro results showed that isoscopoletin inhibited glucose consumption and lactate production, while regulating the levels of glycolysis-related proteins. Conclusion This study suggests that isoscopoletin may exist an anti-tumor effect by regulating the glycolysis-related proteins GPD2, GPI, Hsp90α and PGK2, inhibiting the glycolysis process in HCC cells, then blocking the energy supply of tumor cells.